Development and evaluation of an intervention providing insight into the tobacco industry to prevent smoking uptake: a mixed-methods study - Szatkowski, Lisa; Taylor, John A.; Taylor, Amy; Lewis, Sarah; Britton, John; McNeill, Ann; Bauld, Linda; Wu, Qi; Parrott, Steve; Jones, Laura L.; Bains, Manpreet (NIHR Health Technology Assessment Programme, 2016)
Background